1999
DOI: 10.1136/oem.56.6.391
|View full text |Cite
|
Sign up to set email alerts
|

Long-term respiratory health effects of the herbicide, paraquat, among workers in the Western Cape.

Abstract: Objective-To evaluate the possible effects of paraquat spraying among workers on deciduous fruit farms in the Western Cape, South Africa. Paraquat is a commonly used herbicide world wide and is a well documented cause of pulmonary fibrosis in studies of laboratory animals and in humans after exposure to a high dose (usually accidental or as parasuicide). The respiratory eVects of long term, low dose exposure to paraquat have not been fully evaluated. Methods-A cross sectional study of 126 workers. Administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
43
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 20 publications
4
43
1
Order By: Relevance
“…Dalvie and coworkers did not observe an association of paraquat exposure and respiratory symptoms, spirometry, or carbon monoxide diffusing capacity, but they did report a positive association of chronic paraquat exposure and arterial oxygen desaturation during maximum exercise (20). However, 28% of the saturation traces were considered unreadable, and among those with readable traces the magnitude of the effect was small.…”
mentioning
confidence: 96%
See 3 more Smart Citations
“…Dalvie and coworkers did not observe an association of paraquat exposure and respiratory symptoms, spirometry, or carbon monoxide diffusing capacity, but they did report a positive association of chronic paraquat exposure and arterial oxygen desaturation during maximum exercise (20). However, 28% of the saturation traces were considered unreadable, and among those with readable traces the magnitude of the effect was small.…”
mentioning
confidence: 96%
“…However, the occupational hazards presented by chronic paraquat exposure are less well characterized, and epidemiologic studies have not shown consistent pulmonary changes among paraquat handlers (16)(17)(18)(19)(20). Castro-Gutierrez and colleagues (19) found that exposure to paraquat, as estimated by skin rash symptoms, was related to selfreported respiratory symptoms (chronic bronchitis and episodic dyspnea with wheezing) but they did not observe an association of paraquat exposure with pulmonary function changes measured by spirometry.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Paraquat, a herbicide, is associated with respiratory disorder on high exposure (Dalvie et al, 1999). It shows mild direct mutagenicity and is categorized as a Group E pesticide (showing no evidence of carcinogenicity).…”
mentioning
confidence: 99%